Analysis of Hydrodynamic Performance in Flexitank Applications with Varying Strap Configurations Using CFD - MUHAMMAD HISYAM BIN MOHD AZARAN,; NOFRIZALIDRIS BIN DARLIS,; IZUAN AMIN BIN ISHAK, (Progress in Engineering Application and Technology, 2025)
Liquid sloshing is a fundamental challenge in the structural design offlexitank used for liquid transportation. Thus, flexitank is one of thealternative ways for transporting the fluid package. However, there aresome cases reported by industry regarding the leakage of the flexitankduring transportation. The purpose of this study is to analysis ofhydrodynamic performance in flexitank application with varying strapsconfigurations using CFD software which is Ansys Software. For thegeometry of flexitak, Blender Software are used because it make themodel more 3D. In this study, the straps act like a baffle in the ISO tank.There are several types of straps configurations in this study which arethe number of straps and depths of straps likes one strap, two strapsand three straps for the number of straps, while the depts of straps are1/3, 1/2 and 2/3 of height the flexitank. By simulating theseconfigurations, the research aims to identify optimal designs thatminimize sloshing, improve pressure management, and reduce wallshear stress. The study provides a comprehensive understanding ofhow strap placement influences hydrodynamic forces, contributing tothe development of safer and more efficient flexitank systems for liquidtransportation.